P181 Home pollution monitoring in patients with sleep and respiratory disorders: feasibility and initial data. (December 2018) - Sutherland, F; McDowell, G; Beattie, T; Hastings, A; Carlin, C; Beverland, I
Abstract : Background: Exposure to air pollution is associated with development, progression and exacerbations of respiratory disorders, and overall mortality. Population studies based on estimated or outdoor air pollution levels have also indicated an association between aggravated sleep-disordered breathing (SDB) and increased exposure to particulate matter air pollution. Correlations between SDB variability and air pollution exposure merit further exploration, including to obtain pathophysiological insights, establish potential for sleep monitoring as a pollution biomarker, and to determine if there is a requirement to factor pollution exposure into outcome assessment in sleep therapy trials. We have developed a personal home 7 day pollution monitoring kit to evaluate these and related questions. Methods: Home pollution kit comprising a boxed MicroPEM PM2.5 device with 2 passive diffusion tubes (PDT) has so far been provided to 9 patients (5 normal, 2 OSA, 2 hypoventilation) undergoing sleep studies. Results: Patient feedback on device setup and lack of intrusiveness is reassuring. Home pollution kit is performing reliably. Variability in mean, peak and temporal exposure levels of PM2.5 was notable. Peak indoor PM2.5 exposure exceeded WHO recommended level of 25 ug/m3 in 6 subjects. Exposure spikes at rush hour but also at other times, including early hours of the morning were noted in individual patients. There was no correlation between nitrogen dioxide (NO2) and PM2.5 exposures. Higher indoor NO2 levels were associated with an urban postcode. Conclusions: Home air pollution monitoring is feasible and reliable. Hypothesis-generating insights acquired from 24 hour PM2.5 exposure patterns will be further explored by correlations with sleep study, wearable monitoring physiology and patient outcome data. Initial data from this feasibility study has shown high indoor peak exposure levels of PM2.5 in patients residing across a range of postcodes. This highlights the need for preventative public health measures, but also the value of further developing devices to surface real-time personal pollution monitoring results, to inform harm-reduction strategies.